To solve the equation \( u + \frac{11}{3} = \frac{1}{3} \) using inverse operations, we need to isolate \( u \).
- Subtract \(\frac{11}{3}\) from both sides:
\[ u + \frac{11}{3} - \frac{11}{3} = \frac{1}{3} - \frac{11}{3} \]
This simplifies to:
\[ u = \frac{1}{3} - \frac{11}{3} \]
- Now, we need to perform the subtraction on the right side:
\[ \frac{1}{3} - \frac{11}{3} = \frac{1 - 11}{3} = \frac{-10}{3} \]
So, we have:
\[ u = -\frac{10}{3} \]
Now let's match this solution with the given choices:
A) \(-\frac{10}{3}\)
B) -4
C) \(\frac{10}{3}\)
D) 4
The correct answer is A) \(-\frac{10}{3}\).